A phase 1 dose‐escalation study of filanesib plus bortezomib and dexamethasone in patients with recurrent/refractory multiple myeloma. Issue 21 (19th July 2016) - Chari, Ajai; Htut, Myo; Zonder, Jeffrey A.; Fay, Joseph W.; Jakubowiak, Andrzej J.; Levy, Joan B.; Lau, Kenneth; Burt, Steven M.; Tunquist, Brian J.; Hilder, Brandi W.; Rush, Selena A.; Walker, Duncan H.; et al.
Abstract : BACKGROUND: Filanesib is a kinesin spindle protein inhibitor that has demonstrated encouraging activity in patients with recurrent/refractory multiple myeloma. Preclinical synergy with bortezomib was the rationale for the current phase 1 study. METHODS: The current study was a multicenter study with an initial dose‐escalation phase to determine the maximum tolerated dose of 2 schedules of filanesib plus bortezomib with and without dexamethasone, followed by a dose‐expansion phase. RESULTS: With the addition of prophylactic filgastrim, the maximum planned dose was attained: 1.3 mg/m 2 /day of bortezomib plus 40 mg of dexamethasone on days 1, 8, and 15 of a 28‐day cycle, with filanesib given intravenously either at a dose of 1.5 mg/m 2 /day (schedule 1: days 1, 2, 15, and 16) or 3 mg/m 2 /day (schedule 2: days 1 and 15). The most common adverse events (assessed for severity using version 4.0 of the National Cancer Institute Common Terminology Criteria for Adverse Events) were transient, noncumulative neutropenia and thrombocytopenia with grade 3/4 events reported in 44% (16% in cycle 1 with filgastrim) and 29% of patients, respectively. A low (≤11%) overall rate of nonhematological grade 3/4 toxicity was observed. With a median of 3 prior lines of therapy and 56% of patients with disease that was refractory to proteasome inhibitors, the overall response rate was 20% (55 patients), and was 29% in 14 patients with proteasome inhibitors‐refractory disease receiving filanesib at a dose of ≥1.25 mg/m 2 (duration of response, 5.2 to ≥21.2 months). CONCLUSIONS: The current phase 1 study established a dosing schedule for the combination of these agents that demonstrated a favorable safety profile with a low incidence of nonhematologic toxicity and manageable hematologic toxicity. The combination of filanesib, bortezomib, and dexamethasone appears to have durable activity in patients with recurrent/refractory multiple myeloma. Cancer 2016;122:3327–3335 . © 2016 American Cancer Society . Abstract : The current study reports on the results of a phase 1, multicenter, dose‐escalation study of filanesib in combination with bortezomib, with or without dexamethasone, in patients with recurrent/refractory multiple myeloma. The combination appears to be well tolerated and has demonstrated durable activity in patients with recurrent/refractory myeloma.